Analysing Innovation in Indigenous News: Deaths Inside. (18th August 2021) - Nolan, David; Waller, Lisa
ABSTRACT: In 2018, The Guardian won the award for Innovation at the Walkleys, Australia's most prestigious awards for journalism, for its data journalism project, Deaths Inside, which has catalogued 164 Aboriginal and Torres Strait Islander deaths in custody between 2008 and 2020. This article takes a case study approach to explore the changing relations that have contributed to the development of Deaths Inside; how these have afforded an expansion of the field of Indigenous news, and how, in both form and content, Deaths Inside takes advantage of opportunities to challenge established traditions and formats of Indigenous news representation. Drawing on critical debates surrounding innovation, we suggest Deaths Inside can be considered "innovative" not simply because it takes advantage of the enhanced affordances of digital technologies for developing experimental forms of journalism. It also, importantly, delivers an enhanced social value that builds upon possibilities for improved representation.